2019
DOI: 10.1111/bor.12372
|View full text |Cite
|
Sign up to set email alerts
|

Subglacial and ice‐marginal landforms in south‐central Ontario: implications for ice‐sheet reconfiguration during deglaciation

Abstract: Regional‐scale, high‐resolution terrain data permit the study of landforms across south‐central Ontario, where the bed of the former Laurentide Ice Sheet is well exposed and passes downflow from irregular topography on Precambrian Shield highlands to flat‐lying Palaeozoic carbonate bedrock, and thick (50 to >200 m) unconsolidated sediment substrates. Rock drumlins and megagrooves are eroded into bedrock and mega‐scale glacial lineations (MSGL) occur on patchy streamlined till residuals in the Algonquin Highlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 96 publications
(400 reference statements)
1
6
0
Order By: Relevance
“…The pattern of SSBs in the Stargard drumlin field compared with the morphology of the land surface preceding the last ice advance reconstructed by Hermanowski (2015) (Figure 6A, B) suggests that the ice flow was to some extent topographically controlled. This pattern is consistent with findings elsewhere (Evans et al, 2008;Kessler et al, 2008;Ross et al, 2009;Winsborrow et al, 2010;Rignot et al, 2011;Margold et al, 2015;Fransner et al, 2017;Mulligan et al, 2019), although areas where bed topography exerted little influence on the ice flow are also known (Ross et al, 2009;Stokes et al, 2013b). The relief difference in the area overridden by the drumlinizing ice stream was up to~70 m ( Figure 6B), which is significant given the location of this terrain at the ice-sheet periphery where the ice was thin.…”
Section: Discussionsupporting
confidence: 89%
“…The pattern of SSBs in the Stargard drumlin field compared with the morphology of the land surface preceding the last ice advance reconstructed by Hermanowski (2015) (Figure 6A, B) suggests that the ice flow was to some extent topographically controlled. This pattern is consistent with findings elsewhere (Evans et al, 2008;Kessler et al, 2008;Ross et al, 2009;Winsborrow et al, 2010;Rignot et al, 2011;Margold et al, 2015;Fransner et al, 2017;Mulligan et al, 2019), although areas where bed topography exerted little influence on the ice flow are also known (Ross et al, 2009;Stokes et al, 2013b). The relief difference in the area overridden by the drumlinizing ice stream was up to~70 m ( Figure 6B), which is significant given the location of this terrain at the ice-sheet periphery where the ice was thin.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have demonstrated significant spatial and morphological variability of subglacial landforms, for example, due to changing basal thermal regimes and the dynamic behaviour of ice sheets (e.g. Mulligan et al 2019;Evans et al 2020). In examining the geomorphic characteristics of murtoos, it is important to recognize that a distinction between murtoo-type 'end members' (Fig.…”
Section: Geomorphological Evidence Of Subglacial Formationmentioning
confidence: 99%
“…This palaeoglaciological signature has been likened to the terrestrial equivalent of ice stream/troughmouth fan systems of submarine settings (Evans et al, 2012), and on the prairies is representative of marginal lobation and partial overprinting along the termini of fast ice flow corridors (Patterson, 1997(Patterson, , 1998Colgan et al, 2003;Jennings, 2006;Evans et al, 2008;Ó Cofaigh et al, 2010;Margold et al, 2015;Norris et al, 2018). The role of surging and changing basal thermal regimes in driving spatial and temporal variability in landsystems associated with lobate ice stream margins are being increasingly emphasised as higher resolution geomorphological mapping is undertaken (e.g., Mooers, 1990;Colgan et al, 2003;Evans et al, 2014Evans et al, , 2016aSookhan et al 2018;Mulligan et al 2019). Additionally, thinning and recession of these ice margins occurred down the adverse slope of the regional drainage gradient, which promoted the development of large proglacial lakes, gave rise to complex meltwater drainage patterns and ice-contact glacifluvial features (Christiansen, 1979;Kehew and Lord, 1986;Evans, 2000;Clayton et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%